Seeing Sarah Bernhardt : performance and silent film - Duckett, Victoria (Urbana ; Chicago : University of Illinois Press, 2015)
"The most famous stage actress of the nineteenth century, Sarah Bernhardt enjoyed a surprising renaissance when the 1912 multi-reel film Queen Elizabeth brought her international acclaim. The triumph capped her already lengthy involvement with cinema while enabling the indefatigable actress to reinvent herself in an era of technological and generational change. Placing Bernhardt at the center of the industry's first two decades, Victoria Duckett challenges the perception of her as an anachronism unable to appreciate film's qualities. Instead, cinema's substitution of translated title cards for her melodic French deciphered Bernhardt for Anglo-American audiences. It also allowed the aging actress to appear in the kinds of longer dramas she could no longer physically sustain onstage. As Duckett shows, Bernhardt contributed far more than star quality. Her theatrical practice on film influenced how the young medium changed the visual and performing arts. Her promoting of experimentation, meanwhile, shaped the ways audiences looked at and understood early cinema. A leading-edge reappraisal of a watershed era, Seeing Sarah Bernhardt tells the story of an icon who bridged two centuries--and changed the very act of watching film."--Publisher's description.
Nullius in verba: acting on silent film -- Hamlet: a short film, 1900 -- Camille: the ladies of the Camellias -- Queen Elizabeth: a moving picture, 1912 -- Sarah Bernhardt at home: cinema and the home, circa 1915 -- Mothers of France: World War I, film, and propaganda -- Conclusion.
Includes bibliographical references and index.
Description based on print version record.
English.
JSTOR
Keywords: Bernhardt, Sarah, -- 1844-1923.; Bernhardt, Sarah, -- 1844-1923; Motion picture industry -- France -- History; Silent films -- France -- History and criticism; Cinéma -- Industrie -- France -- Histoire; Films muets -- France -- Histoire et critique; PERFORMING ARTS -- Film & Video -- History & Criticism; PERFORMING ARTS -- Theater -- General; Motion picture industry; Motion pictures; Silent films; France; Drama; Music, Dance, Drama & Film; Criticism, interpretation, etc; History